Unveiling Female Agency in K-pop Demon Hunters: A Postfeminist Perspective - Vivin Amelia; Pratiwi Retnaningdyah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines the construction of female agency in K-Pop Demon Hunters through a postfeminist perspective, focusing on the character of Rumi as a subject shaped by both external expectations and internal conflict. Drawing on Judith Butler’s theory of gender performativity and Gayatri Chakravorty Spivak’s concept of voice and representation, this research explores how Rumi’s identity is negotiated within the pressures of idol culture, familial expectations, and interpersonal relationships. Using a thematic analysis, the study analyzes key scenes that illustrate Rumi’s performative expressions, including silence, controlled speech, and bodily behavior. The findings reveal that Rumi’s identity is not autonomous but constructed through repeated performances regulated by dominant discourses. Her silence and constrained expression reflect structural limitations on her voice, while her gradual shift in behavior demonstrates the emergence of agency as a negotiated process rather than an inherent attribute. From a postfeminist perspective, the study highlights the contradiction between empowerment and regulation, where Rumi appears strong and capable yet remains bound by expectations of perfection, self-control, and emotional restraint. Ultimately, this research argues that female agency in K-Pop Demon Hunters is dynamically produced through the interaction between constraint and self-definition, offering insight into the representation of women in contemporary popular culture.